On-farm Assessment of Medium Duration Rice (Oryza sativa L.) Cultivars for Growth, Yield, Economics and Stress Tolerance - Samant, Tiryak Kumar; Swain, Susanta Kumar (International Journal of Bio-resource and Stress Management, 2020)
A field trial was conducted during kharif season(June to November) of 2017 at farmers’ field by Krishi Vigyan Kendra, Angul of Odisha state, India with an objective to evaluate growth, yield, economics and stress tolerance in 3 medium duration rice cultivars through on farm testing using randomized block design with ten replications. The higher yield of rice cultivar Hiranmayee (48.6 q ha-1), contrasted with lower yielding Surendra (45.2 q ha-1) and MTU 1001 (43.5 q ha-1), resulted from higher tillering ability (16.2 hill-1), effectivity of tillers (88.74%), panicle length (26.7 cm), grains panicle-1 (151.64), spikelet fertility (94.1%),1000 grain weight (22.74 g), straw yield (57.88 q ha-1), harvest index (45.69%) and longer maturation period (134.8 day) which also recorded higher plant height (108.39 cm), dry matter accumulation (916.22 g m-2) and dry matter efficiency (0.394% day-1). Hiranmayee performed better in spite of occurrence of frequent dry spells during different crop growth stages for its genetic potentiality and had higher growing degree days (2412.15), photo-thermal units (32322.81), heat use efficiency (0.38), net return (Rs. 30575.07 ha-1), benefit- cost ratio (1.60) and profitability (Rs. 83.76 ha-1 day-1) than Surendra and MTU 1001. The highest positive correlation were observed between days to maturity with GDD (1.0) and PTU (1.0). Based on the study, it may be concluded that medium duration rice cultivar Hiranmayee was superior to Surendra and MTU 1001 due to higher tillering ability, drought tolerant capacity, growing degree days, heat use efficiency, grain yield and additional net return. Thus, it can replace the old cultivars in the existing farming situation for higher productivity and income.